Apex Court flip flop on basic structure doctrine: a review of Maria Chin v Director General of Immigration [2021] 1 MLJ 750 - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha; Ahmad, Muhamad Hassan (2021)
Malaysia upholds the constitutional supremacy as per Article 4(1) of the Federal Constitution. The constitution provides for the three main organs of the State, namely, the executive, the legislature and the judiciary pursuant to Articles 39, 44 and 121, respectively. The doctrine of separation of power serves as a check against the abuse of power. The greatest challenge in any democratic nation is to balance the might of the State with the rights of its citizens. Article 124 of the Constitution deals with the oath of office and allegiance for the judiciary in which judges of the superior courts are obliged ‘to preserve, protect and defend the Constitution’. Further, the doctrine of basic structure, which has gained widespread acceptance in India since the early 1970’s, dictates that the constitution has certain basic features that cannot be altered or destroyed through amendments by the Parliament and the judiciary is empowered to strike down an amendment to the constitution and Acts enacted by the Parliament which conflict with or seek to alter this basic structure of the constitution. In relation to this issue it would be worthwhile to review the majority and minority’s opinion in Maria Chin case in relation to this doctrine and also to revisit the horizontal application of the stare decisis doctrine with a view of addressing the Federal Court’s flip-flop in relation to this doctrine.